Identification of fake news using machine learning in distributed system - Saif, Mehruz; Kanon, MD. Kamal Haque; Hasan, Nazmul; Hossen, MD. Shamim; Anannya, Fatema Zohra (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.